Rationally engineered double substituted variants of Yarrowia lipolytica lipase with enhanced activity coupled with highly inverted enantioselectivity towards 2-bromo phenyl acetic acid esters - Cambon, Emmanuelle; Piamtongkam, Rungtiwa; Bordes, Florence; Duquesne, Sophie; André, Isabelle; Marty, Alain (Biotechnology and bioengineering, 2010)
Inverting enzyme enantioselectivity by protein engineering is still a great challenge. Lip2p lipase from Yarrowia lipolytica, which demonstrates a low S-enantioselectivity (E-value = 5) during the hydrolytic kinetic resolution of 2-bromo-phenyl acetic acid octyl esters (an important class of chemical intermediates in the pharmaceutical industry), was converted, by a rational engineering approach, into a totally R-selective enzyme (E-value > 200). This tremendous change in selectivity is the result of only two amino acid changes. The starting point of our strategy was the prior identification of two key positions, 97 and 232, for enantiomer discrimination. Four single substitution variants were recently identified as exhibiting a low inversion of selectivity coupled to a low-hydrolytic activity. On the basis of these results, six double substituted variants, combining relevant mutations at both 97 and 232 positions, were constructed by site-directed mutagenesis. This work led to the isolation of one double substituted variant (D97A-V232F), which displays a total preference for the R-enantiomer. The highly reversed enantioselectivity of this variant is accompanied by a 4.5-fold enhancement of its activity toward the preferred enantiomer. The molecular docking of the R- and S-enantiomers in the wild-type enzyme and the D97A-V232F variant suggests that V232F mutation provides a more favorable stacking interaction for the phenyl group of the R-enantiomer, that could explain both the enhanced activity and the reversal of enantioselectivity. These results demonstrate the potential of rationally engineered mutations to further enhance enzyme activity and to modulate selectivity. Biotechnol. Bioeng. 2010;106: 852-859.